Extraction and isolation of xanthine oxidase inhibitors from carica papaya leave extract using chromatographic techniques - Jamal, Parveen; Azmi, Saiful Mohammad Nizam; Amid, Azura (IIUM Press, 2016)
Xanthine oxidase (XO) is a key enzyme that catalyses the oxidation of oxypurines (hypoxanthine and xanthine) to uric acid in the purine metabolic pathway.The increase level of uric acid in the blood serum is called hyperuricemia. Its major complications are gout, urolithiasis and reactive oxygen production. In addition, some diseases are frequently seen with elevated uric acid concentration such as cardiovascular disease and renal insufficiency (Nakagawa et al., 2006), although no direct role has yet been confirmed. Xanthine oxidase inhibitor (XOI) could block the biosynthesis of uric acid from purine in the body, which should be one of the therapeutic approaches for treating hyperuricemia.